O fenômeno hallyu e as práticas interacionais dos fãs brasileiros no contexto do processo do soft power da Coreia do Sul - Almeida, Naiane Batista de (2019)
The South Korean cultural spread phenomenon denominated Hallyu or the Korean Wave, was created in the end of 1990 decade with the purpose of developing an agile dialogue among many countries, using a strategy of develoment based on soft power precepts, which aims on promoting a country through the attraction of their cultural goods. Nowadays the use of hybridity in concepting the goods and the mediation in the fans comunities are important aspects to establish and spread this phenomenon in the International Market. Therefore, this work aims at analysing the international practices as well as the organization of the Brazilian fans communities in the spread of the Hallyu phenomenon from the perspective of the diffusion of tv series, music and beauty known as K-dramas, K-pop, and K-beauty. Applying the deductive method, from the whole to the individual, we explored the appearance of the phenomenon in the Asian continent, the expansion to the West through the fandoms propagation til the arrival in Brazil. Through the research we perceived that the diffusion by the fans stimulated the growth and the visibility of the Korean wave in the Brazilian Society, so as the formation of new identities.